Associations between maternal long-chain polyunsaturated fatty acid concentrations and child cognition at 7 years of age: The MEFAB birth cohort. (November 2017) - Brouwer-Brolsma, E.M.; van de Rest, O.; Godschalk, R.; Zeegers, M.P.A.; Gielen, M.; de Groot, R.H.M.
Abstract: Introduction: Concentrations of the fish fatty acids EPA and DHA are low among Dutch women of reproductive age. As the human brain incorporates high concentrations of these fatty acids in utero, particularly during third trimester of gestation, these low EPA and DHA concentrations may have adverse consequences for fetal brain development and functioning. Methods: Analyses were conducted using longitudinal observational data of 292 mother-child pairs participating in the MEFAB cohort. Maternal AA, DHA, and EPA were determined in plasma phospholipids - obtained in three trimesters - by gas-liquid chromatography. Cognitive function was assessed at 7 years of age, using the Kaufman Assessment Battery for Children, resulting in three main outcome parameters: sequential processing (short-term memory), simultaneous processing (problem-solving skills), and the mental processing composite score. Spline regression and linear regression analyses were used to analyse the data, while adjusting for potential relevant covariates. Results: Only 2% of the children performed more than one SD below the mental processing composite norm score. Children with lower test scores (<25%) were more likely to have a younger mother with a higher pre-gestational BMI, less likely to be breastfed, and more likely to be born with a lower birth weight, compared to children with higher test scores (≥25%). Fully-adjusted linear regression models did not show associations of maternal AA, DHA, or EPA status during any of the pregnancy trimesters with childhood sequential and simultaneous processing. Conclusion: Maternal fatty acid status during pregnancy was not associated with cognitive performance in Dutch children at age 7. Highlights: EPA and DHA intakes are low among Dutch women of reproductive age. Pre-clinical studies suggest adverse effects of low maternal EPA and DHA intakes on fetal brain health. Up to now, human studies examining maternal EPA and DHA status in relation to child brain health are inconclusive. In this study, maternal fatty acid status in the 1st, 2nd or 3rd trimester was not associated with cognitive performance in Dutch children at age 7.